Patrimônio cultural de Rio Pardo/RS: a educação patrimonial como mediadora dos conflitos entre o tombamento e a salvaguarda patrimonial - Louzado, Eduardo Alexandre (2017)
This work of research and analytical study aimed to investigate the historical material cultural heritage of the city of Rio Pardo / RS to, from the existing reality, gather, list and organize subsidies in order to propose as a final product of this research a course Cultural Heritage, teachers and teachers of the municipal public network, municipal managers and the community in general. This course aims at thinking about Heritage Education that will enable citizens to recognize history and collective memory within the cultural milestones of that city. The research presents as basic foundation the concepts for the study of Heritage Education, having as a cut the municipal public policies of foment to Patrimonial Education in the formal education, for the public network of education of the municipality, between the years 2010 to 2016. Methodologically, qualitative research was used, with exploratory research in documental and bibliographic surveys. The technique of direct observation was used to recognize the cultural heritage listed and circumscribed in the perimeter of the Historic Center of the municipality. The data obtained during the investigative process revealed that during the period under analysis there was no implementation of public policy to promote Heritage Education in the municipal school network. Considering that Heritage Education is a relevant practice for the construction of citizenship and safeguard of patrimonial assets located in the Historical Center of the municipality, the result of this research is intended to subsidize schools, educators and managers of the municipality in the formulation of educational public policies with views to continued teacher education punctuated in the cultural heritage of the municipality.